Electronic Digital Signature Protocol of an Asymmetric Encryption Algorithm Based on the Complexity of Performing Actions About Elliptic Curve Points and Multiplication of Matrices with a Parameter on a Final Field - Akhmadaliev Shakhobidin Sharifovich (Zien Journals, 2022)
In article the report of the electronic digital signature on the basis of asymmetric algorithm of the enciphering based on complexity of performance of operation of addition of points with rational coordinates of an elliptic curve on a final field at which, in process formation of the digital signature possibility a choice of any number from the signed is provided is developed
Keywords: matrix; field; multiplication; rational coordinate point